DyIII single-molecule magnets from ligands incorporating both amine and acylhydrazine Schiff base groups: the centrosymmetric Dy2 displaying dual magnetic relaxation behaviors. Issue 44 (4th November 2020) - Su, Sen-Da; Li, Jia-Xin; Xu, Fan; Wang, Chen-Xiao; Wang, Kai; Li, Yan; Zhang, Shu-Hua; Zhang, Xiu-Qing; Zhang, Yi-Quan; Liang, Fu-Pei
Abstract : Using ligands incorporating both amine and acylhydrazine Schiff base groups, two Dy2 and a Dy6 SMMs are synthesized. Two Dy2 show dual magnetic relaxation behaviors, which could be ascribed to the joint contributions of single ion anisotropy and magnetic interactions. Abstract : The novel multidentate chelating ligands N ′-(2-pyridylmethylidene)-2-(2-pyridylmethylideneamino)benzohydrazide (Hpphz) and N ′-(2-salicylmethylidene)-2-(2-salicylmethylideneamino)benzohydrazide (H3 sshz), which incorporate both amine and acylhydrazine Schiff base groups, were synthesized and investigated in Dy III coordination chemistry. The reactions of Hpphz and Dy(OAc)3 ·4H2 O have yielded two Dy2 featuring double OAc − bridges: [Dy2 (H2 aphz)2 (OAc)4 (ROH)2 ] [R = Me (1 ) and Et (2 )], where the Hpphz ligands were in situ hydrolyzed into 2-amino-(2-pyridylmethylideneamino)benzohydrazide ions (H2 aphz − ). Besides, the reaction between H3 sshz and Dy(NO)3 ·6H2 O afforded a [Dy6 (sshz)4 (μ3 -OH)4 (μ4 -O)(MeOH)4 ]2 ·17.5MeOH·2H2 O cluster (3 ). This cluster contained two discrete Dy6 cores, each of which consisted of a pair of Dy3 triangular units. All the complexes displayed a single relaxation process of single-molecule magnet (SMM) behaviors under a zero dc field. Both 1 and 2 showed field-induced dual magnetic-relaxation behaviors. However, their diluted samples (1@Y and 2@Y ) only showed one-step relaxation behaviors whether under a zero or applied dc field, indicating that the dual magnetic-relaxation behaviors of 1 and 2 were absent after the dilution. Combined with ab initio calculations, it could be infered that the dual magnetic-relaxation behaviors of 1 and 2 might be ascribled to the joint contributions of the single ion anisotropy and magnetic interactions. Examples of this type are rather rare in previous studies. Ab initio calculations also suggested that the discrepancy between the relaxation processes of 1 and 2 may be caused by the small difference between their magnetic interactions.